The Quest of African American Modern Culture - Ben Attia, Ibrahim; Temzour ,Mohamed; Aisha ,Hocine (Faculty of Letters and Foreign Languages Department of English, 2019)
The Black culture created hope to determine their personal freedom, to escape the poor living conditions of Blacks, and to create their own identity. African Americans used their culture as a way to express their needs through their artistic works. This study focuses on the how African American culture has manifested itself in America, and how the Afro Americans used their culture to express themselves, and fight for freedom to achieve the aims of the study, the descriptive, qualitative and analytical approaches are adopted. This research attempts to study the modern African American culture through their literature, music, language, and religion. The researchers saw the originality and the uniqueness use of culture in the fight for freedom in the Black culture in America, the integration of Black identity in their culture, and how Afro-American culture is a reflection of their lives in America. The study is structured, chronologically in three chapters, the first chapter attempts to answer the question if the African American claimed their freedom or it was given to them; it gives a historical background about how the African American freedom from slavery, the second chapter, however, illustrates the African American modern culture in four different cultural aspects; language, literature, music and religion, in the last chapter the study aims to cover and illustrate how the White Americans and the US government reacted to African American cultural quest